2024
DOI: 10.3390/su16041563
|View full text |Cite
|
Sign up to set email alerts
|

Innovation-Driven E-Commerce Growth in the EU: An Empirical Study of the Propensity for Online Purchases and Sustainable Consumption

Elżbieta Roszko-Wójtowicz,
Gagan Deep Sharma,
Barbara Dańska-Borsiak
et al.

Abstract: The e-commerce sector has experienced significant growth in the past two decades, outpacing other economic sectors and contributing to sustainable consumption, increased labour productivity, competitiveness, consumer incomes, and GDP growth. This trend is expected to continue, making e-commerce a key driver of sustainable economic growth in Europe. This study aims to explore the relationship between a nation’s innovation level and its population’s inclination towards online shopping in various EU member states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 133 publications
0
0
0
Order By: Relevance
“…Moreover, enterprises can leverage data-driven insights to identify key social influencers and micro-influencers within millennial social networks, and then partner with them to amplify their brand messaging and reach (Cao, 2021) (Tripathi et al, 2021). This influencer marketing strategy has been shown to be particularly effective in engaging millennial consumers (Roszko-Wójtowicz et al, 2024). Furthermore, omni-channel data integration and analytics capabilities enable enterprises to deliver seamless, personalized customer experiences across multiple touchpoints.…”
Section: Literature Review 21 Overview Of Data-driven Marketing Efficacymentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, enterprises can leverage data-driven insights to identify key social influencers and micro-influencers within millennial social networks, and then partner with them to amplify their brand messaging and reach (Cao, 2021) (Tripathi et al, 2021). This influencer marketing strategy has been shown to be particularly effective in engaging millennial consumers (Roszko-Wójtowicz et al, 2024). Furthermore, omni-channel data integration and analytics capabilities enable enterprises to deliver seamless, personalized customer experiences across multiple touchpoints.…”
Section: Literature Review 21 Overview Of Data-driven Marketing Efficacymentioning
confidence: 99%
“…Recent study done by Roszko-Wójtowicz et al (2024) found that millennials respond more favorably to marketing campaigns that are personalized and delivered through their preferred digital and mobile channels, as these approaches align with their expectations for tailored, on-demand experiences.…”
Section: Data-driven Personalization and Omni-channel Integrationmentioning
confidence: 99%
See 3 more Smart Citations